W obronie infanta Edwarda – druki z kolekcji portugalskiej Biblioteki Narodowej [Biblioteca Nacional de Portugal] i wybrane aspekty ramy literacko-wydawniczej - Działak-Szubińska, Anna (Collectanea Philologica, 2024)
This paper focuses on one important aspect of the Post(-Restoration) period (1640–1668) in Portugal, i.e. the defense of D. Duarte of Portugal (1605–1649), brother of the Portuguese king, John IV. As the Restoration War set two kingdoms – Spain and Portugal against each other – D. Duarte was kept prisoner in the Castello Sforzesco in Milan. The paper examines a literary aspect of D. Duarte’s story. It is based on a corpus retrieved from the National Library of Portugal that contains 19 texts published between 1641 and 1652, in different languages, and representative of different literary genres. Following Gustavo Kelly de Almeida (2011), who analysed a similar corpus at the National Library of Brasil [Biblioteca Nacional do Brasil], and Vanda Anastácio’s (2007) insights, the paper shows how the prints uphold the fight to liberate D. Duarte of Portugal. To make it clear, the paper offers a paratextual study of selected prints. At the same time the paper studies the importance of fixed formulas and topoi versus political utility and individualised elements.